Sistem Informasi Administrasi Service Kendaraan Bermotor Dan Katalog Spare Part Berbasis Web Dengan Teknologi Single Page Application (SPA) - Fahrudin, Irfan Nur, Dr.Ir. Bana Handaga,M.T (2016)
System administration on workshop manual Olisa Motor still need to be converted into a computerized administration system workshop to facilitate the operational activities in the workshop. With computerized administrative systems, the data generated will be faster and more accurate. The purpose of this research is to create a computerized administration system workshop. Stages in the completion of this study consisted of a needs analysis, system design, implementation, system implementation and system maintenance. Making the system using the PHP programming language and MySQL database. Results of the system that has been created is a form of administrative system repair shop that can manage data service vehicles ranging from the input of customer data, the input data is the vehicle, the registration service, manufacturing work order (PKB), invoicing, sales management of spare parts and preparing reports income. Besides, the system is also designed to give relevant information to potential buyers of spare parts catalog is available in the garage through the website. The use of technology on a single page application aims to make the website faster website performance and responsive. Based on the assessment questionnaire answers that have been distributed to the respondents, 80% stated that the resulting system is able to simplify data management service vehicles and 80% of the system can facilitate the manufacture of earnings reports and invoices quickly, helping facilitate the operational activities of the workshop.